2007
DOI: 10.1260/135101007781448037
|View full text |Cite
|
Sign up to set email alerts
|

Sounds from the Past the Acoustics of Sultan Hassan Mosque and Madrasa

Abstract: The Sultan Hassan Mosque and Madrasa is considered to be stylistically the most compact and unified of all of Cairo's Islamic monuments. Beside its main function as a place for prayer, its design also allows separate schools for teaching the four Sunni rites; both functions imply the importance of phonological cognition and intelligibility of speech. The acoustical environment within the main Iwan of the Madrasa and Mosque of Sultan Hassan has been investigated and examined through field measurements and room … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 8 publications
2
30
0
Order By: Relevance
“…The outcomes were analyzed and compared to another studies done for Catholic churches and mosques within volume average; in general, the average RT was 500-1 kHz but was a little higher when compared to the value recommended by the authors. El-khateeb and Ismail [4] studied the speech intelligibility in Sultan Hassan Mosque and Madrasa situated in Cairo, Egypt, by field measurements and ODEON simulation. The parameters were RT and Speech Transmission Index (STI) for occupied and unoccupied cases.…”
Section: Studies On Analysis Of Existing Mosquesmentioning
confidence: 99%
“…The outcomes were analyzed and compared to another studies done for Catholic churches and mosques within volume average; in general, the average RT was 500-1 kHz but was a little higher when compared to the value recommended by the authors. El-khateeb and Ismail [4] studied the speech intelligibility in Sultan Hassan Mosque and Madrasa situated in Cairo, Egypt, by field measurements and ODEON simulation. The parameters were RT and Speech Transmission Index (STI) for occupied and unoccupied cases.…”
Section: Studies On Analysis Of Existing Mosquesmentioning
confidence: 99%
“…Such studies may include single mosque cases [17,20,21,22] or some of them include comparisons of mosques to other mosques [14,16,19,23,24,25,26] or comparisons of mosques to other worship spaces (churches and/or synagogues) [27].…”
Section: Acoustical Requirements In Mosquesmentioning
confidence: 99%
“…In this case, as opposed to eqn. (5), results showed that l is inversely proportionate to T. (14) investigated the acoustical performance in five common shapes (rectangle, trapezoid, square, hexagon and octagon) of the contemporary traditional Masjids utilizing computer models. The forms of the chosen samples were right prisms.…”
Section: Related Workmentioning
confidence: 99%